Southeast Asian ecocriticism theories, practices, prospects - Ryan, John (John Charles) (Poet) (Ecocritical theory and practice, 2018)
"This book offers a timely exploration into the rapidly growing field of ecocriticism and gives prominence to the writers, creators, theorists, traditions, concerns, and landscapes of Southeast Asia. The contributors emphasize the transnational flows between Southeast Asian countries and Australia, England, Taiwan (Formosa), and the United States"--Provided by publisher.